'Aquí viene una Veneca más': Venezuelan migrants and 'the sexual question' in Peru. Issue 3 (3rd July 2022) - Irons, Rebecca
Abstract: Migrant access to sexual and reproductive health (SRH) services has been highlighted as an urgent priority for the 800, 000+ Venezuelans who have arrived in Peru in recent years due to political and economic crisis. Venezuelan migrants in Peru, however, negotiate their access to SRH services in what anthropologists term a 'geography of blame', and are accused and stigmatised for having imported sexually transmitted infections to the local population. Alongside this blame, female migrants are highly sexualised and face stigma, resulting in real and perceived threats to their safety, wellbeing, and integration. By juxtaposing ethnographic research and 50 interviews conducted with female migrants living in Lima, their Limeño neighbours, and with local NGOs, the paper argues how stigma is itself a neglected public health issue. Addressing SRH needs for Venezuelan migrants is not only a question of rolling out health campaigns or providing pills, but that underlying social issues such as sexualisation and stigma need to also be recognised and incorporated into policy.